Nghiên cứu tính chất hóa lý của vật liệu mao quản trung bình Ti-SBA-15 được tổng hợp bằng phương pháp trực tiếp - Đức, Hoàng Văn; Phương, Đặng Tuyết; Phú, Nguyễn Hữu (Vietnam Journal of Chemistry, 2014)
Ti-containing SBA-15 mesoporous (Ti-SBA-15) materials have been successfully synthesized by direct method. The prepared Ti-SBA-15 samples were characterized by powder X-ray diffraction (XRD), transmission electron microscopy (TEM), nitrogen adsorption/desorption measurement, diffuse reflectance UV-visible spectroscopy (UV-Vis) and scanning electron microscopy (SEM). The obtained results have shown that the prepared samples had highly ordered hexagonal mesostructure with large specific surface area and uniform mesopore size distribution. No damage to the SBA-15 silica mesostructures was caused by the loading of titanium in framework. Ti substituted for Si in framework of SBA-15 existed in tetrahedrally coordinated form